A 3D multi-cellular tissue model of the human omentum to study the formation of ovarian cancer metastasis. (March 2023) - Estermann, Manuela; Coelho, Ricardo; Jacob, Francis; Huang, Yen-Lin; Liang, Ching-Yeu; Faia-Torres, Ana Bela; Septiadi, Dedy; Drasler, Barbara; Karakocak, Bedia Begum; Dijkhoff, Irini Magdelina; Petri-Fink, Alke; Heinzelmann-Schwarz, Viola; et al.
Abstract: Reliable and predictive experimental models are urgently needed to study metastatic mechanisms of ovarian cancer cells in the omentum. Although models for ovarian cancer cell adhesion and invasion were previously investigated, the lack of certain omental cell types, which influence the metastatic behavior of cancer cells, limits the application of these tissue models. Here, we describe a 3D multi-cellular human omentum tissue model, which considers the spatial arrangement of five omental cell types. Reproducible tissue models were fabricated combining permeable cell culture inserts and bioprinting technology to mimic metastatic processes of immortalized and patient-derived ovarian cancer cells. The implementation of an endothelial barrier further allowed studying the interaction between cancer and endothelial cells during hematogenous dissemination and the impact of chemotherapeutic drugs. This proof-of-concept study may serve as a platform for patient-specific investigations in personalized oncology in the future.